2018
DOI: 10.1590/1809-4392201704522
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal variation in fire occurrence in the state of Amazonas, Brazil, between 2003 and 2016

Abstract: Wildland fires can be responsible for negative impacts on the environment, causing damage to the fauna and flora and increasing the release of greenhouse gases. In the state of Amazonas, wildland fires represent a risk for biodiversity conservation, since more than 95% of the state is covered by Amazon rainforest, one of the largest and most biodiverse tropical forests of the world. This study aimed to analyze the spatiotemporal variation of fire occurrence from 2003 to 2016 in the state of Amazonas, based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 29 publications
2
20
0
2
Order By: Relevance
“…The variation in the number and density of hot spots detected throughout the South America countries is due to the differences on cultural aspects of the population and on environmental factors that influence fire propagation such as weather conditions, vegetation and topography (SOARES;BATISTA, 2007;WHITE;WHITE, 2016). In a similar study done in the state of Amazonas, Brazil, for example, White (2018) concluded that the municipalities with the highest number of hot spots detected were the ones that presented the largest deforested, pasture and agricultural areas; and were the ones with the lowest mean annual rainfall. According to the same author, the cultural practice of using fire for clearing forests, pastures and agricultural areas during the driest months of the year and, most of the time, without using fire safety measurements, is responsible for a large number of high intensity wildfires that are easily detected by satellite sensors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The variation in the number and density of hot spots detected throughout the South America countries is due to the differences on cultural aspects of the population and on environmental factors that influence fire propagation such as weather conditions, vegetation and topography (SOARES;BATISTA, 2007;WHITE;WHITE, 2016). In a similar study done in the state of Amazonas, Brazil, for example, White (2018) concluded that the municipalities with the highest number of hot spots detected were the ones that presented the largest deforested, pasture and agricultural areas; and were the ones with the lowest mean annual rainfall. According to the same author, the cultural practice of using fire for clearing forests, pastures and agricultural areas during the driest months of the year and, most of the time, without using fire safety measurements, is responsible for a large number of high intensity wildfires that are easily detected by satellite sensors.…”
Section: Discussionmentioning
confidence: 99%
“…In such ecosystems, the incidence of solar radiation in the understory is reduced by the canopy cover and the air humidity is high due to the evapotranspiration of the trees. Consequently, the moisture content of the fuel load is usually high, making it difficult for a fire to ignite and propagate (WHITE;SILVA, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These variables were chosen due to availability of historical data and because they have been shown to influence the wildland fire occurrence (e.g. Ajin et al, 2016;Suryabhagavan et al, 2016;White, 2018b).…”
Section: Datasetsmentioning
confidence: 99%